Achievement of complete remission predicts outcome of allogeneic haematopoietic stem cell transplantation in patients with chronic myelomonocytic leukaemia. A study of the Chronic Malignancies Working Party of the European Group for Blood and Marrow Transplantation. (26th July 2015) - Symeonidis, Argiris; van Biezen, Anja; de Wreede, Liesbeth; Piciocchi, Alfonso; Finke, Juergen; Beelen, Dietrich; Bornhäuser, Martin; Cornelissen, Jan; Volin, Liisa; Mufti, Ghulam; Chalandon, Yves; Ganser, Arnold; et al.
Summary The results of allogeneic stem cell transplantation (allo‐SCT) in chronic myelomonocytic leukaemia (CMML) are usually reported together with other categories of myelodysplastic syndrome. We analysed transplantation outcome in 513 patients with CMML, with a median age of 53 years reported to the European Group for Blood and Marrow Transplantation. Conditioning was standard (n = 249) or reduced‐intensity (n = 226). Donors were human leucocyte antigen‐related (n = 285) or unrelated (n = 228). Disease status at transplantation was complete remission (CR) in 122 patients, no CR in 344, and unknown in 47. Engraftment was successful in 95%. Grades 2–4 acute graft‐versus‐host disease (GvHD) occurred in 33% of the patients and chronic GvHD was reported in 24%. The 4‐year cumulative incidence of non‐relapse mortality was 41% and 32% for relapse, resulting in a 4‐year estimated relapse‐free and overall survival (OS) of 27% and 33%, respectively. Patients transplanted in CR had lower probability for non‐relapse death (P = 0·002) and longer relapse‐free and OS (P = 0·001 and P = 0·005, respectively). In multivariate analysis the only significant prognostic factor for survival was the presence of CR at transplantation (P = 0·005). Allo‐SCT remains a curative treatment option for patients with CMML and should preferably be performed early after diagnosis or after establishing the best possible remission status.